2013
DOI: 10.1177/1056789513511976
|View full text |Cite
|
Sign up to set email alerts
|

Charpy impact response of basalt fiber reinforced epoxy and basalt fiber metal laminate composites: Experimental study

Abstract: In this article, the effect of adding micro glass powder into basalt fiber reinforced epoxy composites on the Charpy impact behavior is investigated by both flatwise and edgewise specimens. Also, the effect of adding micro glass powder at two temperatures is examined on the Charpy impact behavior in order to obtain a more detailed knowledge of the role of micro glass powder in polymer composites. Moreover, the effect of adding metal layers to basalt fiber reinforced epoxy composites with various combinations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…The mechanical properties of FMLs improved with the increase in fiber layers regardless of the types of FML skin layers. Farsani et al . had shown the Charpy impact energy absorption of basalt fiber reinforced aluminum and steel FMLs to be superior compared to their corresponding composites.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mechanical properties of FMLs improved with the increase in fiber layers regardless of the types of FML skin layers. Farsani et al . had shown the Charpy impact energy absorption of basalt fiber reinforced aluminum and steel FMLs to be superior compared to their corresponding composites.…”
Section: Introductionsupporting
confidence: 88%
“…The mechanical properties of FMLs improved with the increase in fiber layers regardless of the types of FML skin layers. Farsani et al [25] had shown the Charpy impact energy absorption of basalt fiber reinforced aluminum and steel FMLs to be superior compared to their corresponding composites. Sivakumar et al [26] conducted Charpy impact test for oil palm fiber reinforced aluminum FMLs with different fiber compositions, ranging from 10 to 60 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber metal laminates (FMLs) can be defined as hybrid composites based on thin metal sheets and fiber reinforced polymer (FRP) layers. [ 1,2 ] Metals can be easily repaired. They have high bearing strength and excellent impact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The response of steel based fiber-metal laminates under various loading conditions is very interesting since steel is a classical construction material and their applications can be numerous. Recently, scientific articles concerning fiber-metal laminates with steel metal layers have been published [1][2][3][4][5][6][7][8][9]. In these articles, various applications are considered: thick walled tubes subjected to axisymmetric internal pressure [9], shear walls for the construction of buildings [6], panels for underwater applications [5] and industrial applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…In these articles, various applications are considered: thick walled tubes subjected to axisymmetric internal pressure [9], shear walls for the construction of buildings [6], panels for underwater applications [5] and industrial applications [4]. The mechanical evaluation of steel based fiber-metal laminates includes their impact response, fatigue characteristics, creep behavior, hygrothermal conditioning, response to earthquake loading [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%